The Role of Teachers in Fostering Student Character Through Holistic Learning at SDIT An-Nahl Depok West Java - Setiowati, Rachmi Endah (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Developing the character of students in elementary school is essential for establishing a solid moral and ethical base. To achieve this objective, SDIT AN-NAHL Depok has implemented a comprehensive learning approach, with teachers playing a pivotal role in the process. This research emphasizes the significance of incorporating character education into the elementary school curriculum to cultivate a generation that values integrity and ethics. This study aims to investigate the impact of teachers on student character development through a comprehensive approach to learning at SDIT AN-NAHL Depok. We used a case study approach, employing a qualitative methodology. We gathered information by observing classrooms, conducting detailed interviews with teachers, and analyzing educational documents. This approach offers a profound understanding of the teaching practices and strategies employed. The findings indicate that educators at SDIT AN-NAHL Depok employ a range of comprehensive approaches, including incorporating ethical principles into the curriculum, implementing project-based learning, and exemplifying positive conduct. Teachers also play a crucial role in fostering a nurturing learning environment that promotes the growth of students' character. They engage students in various activities that cultivate qualities such as empathy, cooperation, and responsibility. This study emphasizes the crucial role of teachers in shaping student character through a comprehensive learning approach. Teachers serve as more than just educators; they also act as facilitators and role models, offering positive examples. This research suggests that it would be beneficial for teachers to receive additional training and professional development in order to enhance their skills in implementing holistic learning. Support from schools and other stakeholders is essential for the success of students' character development through a well-rounded education.